Cohesive Devices in Learners Writing - Nugraheni, Ratnasari (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2015)
In ESL context, learners may have less attention to the use of conjunctions. In fact, theuse of conjunctions in L2 learners writings is crucial since it is one type of cohesivedevices. This paper aims to find the cohesive devices of conjunctions used by thelearners. Through analyzing eight learners essays, the writer found 37 forms and 12types of conjunctions in the learners essays. The most significant form of conjunctionswasand, whereas the most significant types of conjunction as addition. Moreover,the writer also found some inappropriate use of conjunctions, which are groupedinto five, namely, unclassified, wrong mechanism, L1 interference, wrong forms ofconjunctions, and grammatical error.